LAND ACQUISITION FOR PUBLIC INTERESTS DEVELOPMENT: A HUMAN RIGHTS REVIEW - M. Hadyan Yunhas Purba; Siti Nurahmi Nasution; Eva Syahfitri Nasution (Universitas Syiah Kuala, 2022)
Law Number 2 of 2012 states that the acquisition of land for public interests must be accompanied by adequate and fair compensation, as well as the protection and respect of human rights. However, the construction of the Tebing-Tinggi - Kuala Tanjung Toll Road in Sipare-pare and Pasar Lapan Villages, Air Putih Subdistrict, Batu Bara Regency, Indonesia, exemplifies how compensation is frequently unfair. This study seeks to determine the suitability of implementing land acquisition using current laws and regulations. The primary data is gathered through interviews with landowners and the Regional Office of the National Land Agency of the Province of North Sumatra. While secondary data are gathered via literature and legal research. The results revealed that the provided compensation did not meet the requirements of Law No. 2/2012, prompting the public to file an objection with the Kisaran District Court.